Impact of donor sodium levels on clinical outcomes in liver transplant recipients: a systematic review. Issue 12 (December 2020) - Basmaji, John; Hornby, Laura; Rochwerg, Bram; Luke, Patrick; Ball, Ian M
Abstract : We performed a systematic review of the literature to examine the effects of donor sodium levels on liver graft function and recipient survival, as well as to identify the optimal serum sodium target in donors. We searched MEDLINE, Cochrane, and trial registries from 1946 to May 2019 for studies that evaluated the effect of serum sodium levels in neurologically deceased liver donors on transplant outcomes. We used a two-step review process with four independent reviewers to identify relevant articles based on inclusion/exclusion criteria. We summarize the results narratively, assess the risk of bias, and apply the Grading of Recommendations Assessment, Development, and Evaluation methods to evaluate the certainty in the evidence. We included 25 cohort studies were in our final analysis (total n = 19 389). Twenty-two reported on graft function and survival. Summary data suggest an association between donor serum sodium and recipient liver graft dysfunction, with very low certainty in evidence due to serious concerns with risk of bias, inconsistency, indirectness, and imprecision. Seven studies reported on recipient mortality, with results suggesting no association between donor sodium and recipient survival. The certainty in evidence for this outcome was also very low due to serious concerns with imprecision, indirectness, and risk of bias. Donor sodium dysregulation is associated with liver graft dysfunction, but not recipient mortality. Further research is needed to determine the effects of correcting donor sodium levels on transplant outcomes, quantify the dose-response curve, and identify liver recipients most vulnerable to sodium dysregulation. Abstract : Supplemental Digital Content is available in the text.